Global outbreak of deadly measles in 2019 - Mishra, Ved Prakash; Twanabasu, Suraj; Kusma, Susan; Paudel, Sunil (International Journal Of Community Medicine And Public Health, 2019)
Measles is an infection of the respiratory system caused by a virus, especially a Paramyxovirus of the genus Morbillivirus, a single stranded negative sense RNA virus. Infants younger than 12 months, school-aged children or young adults depending upon local immunization practice are highly susceptible for the disease.